Quality of life in gynecological cancer patients: focusing in religious aspects - Mulyono, Wastu Adi; Ekowati, Wahyu; Ningrum, Fera Agusti; Nurhikmah, Salma; Maharani, Nadia Bella (Universitas Muhammadiyah Purwokerto, 2024)
Background: Gynecological cancer is a malignancy that attacks the reproductive organs, affecting not only physical health but also psychological and emotional well-being, often causing depression and anxiety. Religious and spiritual factors have been identified as potential moderators of quality of life in cancer patients.Objective: This study evaluates the relationship between religious aspects spirituality, awareness, and religious coping and quality of life in gynecological cancer patients.Methods: A cross-sectional study involved 61 gynecological cancer patients undergoing chemotherapy at Margono Hospital. Data were collected using validated instruments: FACIT-Sp for spirituality, FMI for awareness, Brief R-Cope for religious coping, PSS-10 for stress, and WHOQOL-BREF for quality of life. The Pearson correlation coefficient was used to assess the relationship between variables.Results: Spirituality (r = 0.434), awareness (r = 0.425), positive religious coping (r = 0.313), and stress (r = -0.515) were significantly correlated with quality of life. Negative religious coping (r = -0.121) showed a negative but non-significant correlation.Conclusions: This study highlights that spirituality, mindfulness, and positive religious coping are significantly associated with improved quality of life in gynecologic cancer patients. These results emphasize the potential role of religious and spiritual support as an integral component of comprehensive cancer care to improve overall patient well-being.